(untitled) (The Agriculturists, 2015)
Variations in growth and yield of three hyacinth bean genotypes collected from Sitakundu of Chittagong, were investigated at the Agricultural Research Station (ARS) of Bangladesh Agricultural Research Institute (BARI), Pahartali, Chittagong during November 2011 to March 2012, where BARI Seem-4 was used as standard control. The minimum number of days for pod formation (54 days) was recorded in BARI Seem-4, while the maximum was in DLP 002 (62 days). The highest number of pods (324) per plant was obtained from DLP 001 followed by DLP 003 (212.33) and the lowest (148.33) was obtained from BARI Seem-4. The maximum weight (12.61 g) of single pod was observed in DLP 003, which is close to that of DLP 002 (12.23 g). The minimum weight of single pod (7.08g) was however observed in DLP 001. Weight of 100-green seed (117.17 g) was maximum in DLP 002, while that of DLP 001 was the minimum (85.90 g).The maximum green seed (61.86 %) was found in DLP 003 and the minimum was in DLP 001 (47.89 %). DLP 003 produced the highest pod yield (26.77 t/ha) which was followed by DLP 001 (22.94 t/ha), while BARI Seem-4 produced the lowest (17.43 t/ha), which is close to that of DLP 002 (19.57 t/ha). The Agriculturists 2014; 12(2) 01-05